2022
DOI: 10.1007/s00167-021-06760-z
|View full text |Cite
|
Sign up to set email alerts
|

Low posterior tibial slope is associated with increased risk of PCL graft failure

Abstract: Purpose To evaluate the efect of posterior tibial slope (PTS) on patient-reported outcomes (PROs) and posterior cruciate ligament (PCL) graft failure after PCL reconstruction. Methods Patients undergoing PCL reconstruction with a minimum 2-year follow-up were included in this retrospective cohort study. A chart review was performed to collect patient-, injury-, and surgery-related data. Medial PTS was measured on preoperative lateral radiographs. Validated PROs, including the International Knee Documentation C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 31 publications
0
16
0
2
Order By: Relevance
“…Decreased PTS was also to be unfavourable to posterior stability in PCL-deicient knees in biomechanical research [28]. In addition, a decreased PTS might adversely afect PCL reconstruction results and it even appears to be an important risk factor for PCL graft failure [4,7,19,37]. Similarly, previous clinical studies also conirmed the beneits of increasing the PTS via tibial osteotomy in PCL-deicient knees [17,35].…”
Section: Discussionmentioning
confidence: 87%
“…Decreased PTS was also to be unfavourable to posterior stability in PCL-deicient knees in biomechanical research [28]. In addition, a decreased PTS might adversely afect PCL reconstruction results and it even appears to be an important risk factor for PCL graft failure [4,7,19,37]. Similarly, previous clinical studies also conirmed the beneits of increasing the PTS via tibial osteotomy in PCL-deicient knees [17,35].…”
Section: Discussionmentioning
confidence: 87%
“…[18]. In another study, a one‐degree decrease in MTS was associated with a 1.3‐fold increase in the odds of PCL graft failure (95% CI, 1.013–1.580, p < 0.05) [25].…”
Section: Resultsmentioning
confidence: 99%
“…Although elevated posterior tibial slope is a risk factor for failed ACL reconstruction, decreased posterior tibial slope increases the risk of failed posterior cruciate ligament (PCL) reconstruction 18,28 and represents an indication for anterior opening-wedge high tibial osteotomy 29,30 . In a recent retrospective cohort study of 79 patients, Winkler et al 28 found a mean posterior tibial slope of 7.0° in patients who underwent failed PCL reconstruction compared with 9.2° in those who did not experience a graft failure. In a case series of 6 patients, Weiler et al 30 described performing an anterior opening-wedge high tibial osteotomy in patients with PCL deficiency and a preoperative posterior tibial slope of 2° to 5°, increasing the slope to a mean of 11.5° postoperatively.…”
Section: Joint Alignmentmentioning
confidence: 99%
“…No graft ruptures occurred at a minimum followup of 2 years. Although elevated posterior tibial slope is a risk factor for failed ACL reconstruction, decreased posterior tibial slope increases the risk of failed posterior cruciate ligament (PCL) reconstruction 18,28 and represents an indication for anterior opening-wedge high tibial osteotomy 29,30 . In a recent retrospective cohort study of 79 patients, Winkler et al 28 found a mean posterior tibial slope of 7.0°in patients who underwent failed PCL reconstruction compared with 9.2°in those who did not experience a graft failure.…”
mentioning
confidence: 99%